The sensorimotor basis of subjective experience in social synchronization behavior - Bremer, Jan P.; Knorr, Marius S.; Göschl, Florian; Maÿe, Alexander; Engel, Andreas K.; Schneider, Till R. (Frontiers in Virtual Reality, 2025)
The sensorimotor contingency (SMC) theory addresses action and perception as constitutive factors to one another–what is being perceived depends on what we do and vice versa. Accordingly, perception is seen as an active process of probing the environment and receiving feedback from it. These action-effect patterns may also be a predominant factor in social interactions. They can manifest in the phenomenon of synchronization, for example, when applause, gait, or posture in conversations synchronize unintentionally and form the basis of the concept of socially deployed sensorimotor contingencies (socSMCs). In this study, we introduce and compare measures used to study complex systems in order to quantify the information-theoretic basis of socSMCs. Two human participants had to synchronize arm movements in a full body virtual reality (VR) environment with each other. We aimed to evaluate the information-theoretic measures transfer entropy and mutual information in this complex motion synchronization task. Furthermore, in our experiment participants shared a mutual sensation of synchronicity and creativity for their interaction solely based on their movements. These subjective ratings of synchronicity and creativity can be predicted using transfer entropy and mutual information, showing that informational coupling between agents is relevant to subjective experience of interaction as described by the concept of socSMCs.